Indian food composition tables - Longvah T; Ananthan, R; et.al (India National Institute of nutrition, 2017)
This book provides detailed information on the nutrient composition of a wide range of common Indian foods available all over India. It also has a write-up on the basic aspects of human nutrition. Keeping food composition date up-to-date is a continuous challenge. This book not only provides data of regular nutrients in foods complete an all respect but also on a whole range of bio-active substances. The tables contain data on oligosaccharides, phytosterols, organic acids and individual polyphenols. It also embodies an exhaustive database on amino acid and fatty acid profiles of various foods in India.
Keywords: Food and drink